2007
DOI: 10.1016/j.dci.2006.04.002
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of the activation of Cg-timp, an immune response component of pacific oysters, through a damage-associated molecular pattern pathway

Abstract: In a previous work, we characterized a Crassostrea gigas cDNA (Cg-timp) encoding a protein which presents all the features of vertebrate tissue inhibitor of metalloproteinase (TIMP). The expression pattern of this gene led us to propose that Cg-timp is an important factor in oyster wound healing and defense mechanisms. Here we describe the analysis of Cg-timp expression in oysters challenged by live or dead bacteria as well as by bacterial secretory/excretory products and metalloproteinase. Surprisingly, bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…In C. gigas, TIMP-like molecules were shown to be upregulated in response to shell damage or infection with Vibrio spp. (Montagnani et al 2001(Montagnani et al , 2007. However, De Decker and Saulnier (2011) as well as Labreuche et al (2006) found strong downregulation or no response to Vibrio spp.…”
Section: Changes Of Gene Expression In the Hemocytes Of Injured Animalsmentioning
confidence: 95%
“…In C. gigas, TIMP-like molecules were shown to be upregulated in response to shell damage or infection with Vibrio spp. (Montagnani et al 2001(Montagnani et al , 2007. However, De Decker and Saulnier (2011) as well as Labreuche et al (2006) found strong downregulation or no response to Vibrio spp.…”
Section: Changes Of Gene Expression In the Hemocytes Of Injured Animalsmentioning
confidence: 95%
“…PAMPs are exclusive to microbes and are not produced by hosts, emerging as indispensable for microbial fitness (Nürnberger et al 2004). Nevertheless, activation of defence mechanisms in oyster species could be triggered not only by PAMPs but also by damage-associated molecular patterns (DAMPs), as defined in the Matzinger damage model , Matzinger 2002, Montagnani et al 2007). Host molecules recognizing PAMPs are called Pattern Recognition Molecules (PRM) or Pattern Recognition Receptors (PRR; .…”
Section: Molecular Immunity Of Bivalvesmentioning
confidence: 99%
“…In C. gigas, Cg-timp is thought to be involved in host immune reactions and tissue repair (Montagnani et al, 2007). In all three tissues tested, we saw a general decrease in Cg-timp transcript abundance in response to bacterial exposure, but only expression changes in gill tissue exhibited a significant decrease (Fig.…”
Section: Expression Of Matrix Metalloproteinase and Coagulantsmentioning
confidence: 64%
“…However, subsequent work suggested that Cg-timp activation in response to infection is independent of a non-self recognition step and its precise role in responding to bacterial infection is unknown (Montagnani et al, 2007).…”
Section: Expression Of Matrix Metalloproteinase and Coagulantsmentioning
confidence: 99%
See 1 more Smart Citation